Detection of Prion Diseases at Early Stages using Genetic Algorithm - Rishika Srivastava; Dr. Anita Pal (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Neurodegenerative disorders are characterized by the progressive deterioration of neuronal function within the brain and spinal cord, leading to cognitive and motor impairments. Among these, prion diseases—caused by the misfolding of prion proteins (PrPSc)—are particularly aggressive and frequently lack early-stage diagnostic biomarkers. Early identification is essential but remains challenging due to the invasive nature of conventional diagnostic procedures. Recent advancements in machine learning, particularly genetic algorithms, offer promising methodologies for analyzing complex biomedical datasets. These approaches have the potential to facilitate timely and accurate diagnosis, thereby improving clinical outcomes.
Keywords: Genetic Algorithm; Machine learning; neurodegenerative diseases; Prion diseases; Diagnosis